Daftar Isi - , No 1 (2014), Vol 7 (Jurnal Energi Dan Manufaktur; Vol 7 No 1 (2014): April 2014, 2015)
Link Vol 7, No 1 (2014): April 2014: http://www.mediafire.com/view/98x4n50ih3vlb0a/JEM_Vol_7_no_1_2014.pdf